2019
DOI: 10.3390/su11246886
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis of the Water Supply Network in the Aspect of Climate Changes on the Example of the Central and Eastern Europe Region

Abstract: The consequences of climate changes are felt by society every day. A sudden increase or decrease in air temperature, increasingly frequent, extreme weather phenomena can cause enormous economic damage to countries and cities. The occurrence of random weather phenomena and their negative impact on technical infrastructure nowadays are the basic problem related to ensuring the safety of the functioning of each system. Climate changes and significant air temperature amplitudes have a direct impact on the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Research indicates that bigger failure frequency of water supply networks is observed in cold periods due to ground freezing, and in hot and dry periods due to increased water consumption, soil shrinkage, and ground settlements [11,17,18,[20][21][22][23]. The strongest relationships between the values of failure rate were observed for the factor associated with daily temperature [11,[16][17][18]24]. As the temperature drops, an increase in the failure rate values of the water supply network is observed.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Research indicates that bigger failure frequency of water supply networks is observed in cold periods due to ground freezing, and in hot and dry periods due to increased water consumption, soil shrinkage, and ground settlements [11,17,18,[20][21][22][23]. The strongest relationships between the values of failure rate were observed for the factor associated with daily temperature [11,[16][17][18]24]. As the temperature drops, an increase in the failure rate values of the water supply network is observed.…”
Section: Introductionmentioning
confidence: 96%
“…Higher failure rates are observed in pipes with high pressure or pipes exposed to big pressure fluctuations [18,19]. There have also been several studies on the impact of climate change on the failure rate of the water supply network [16,18,20,21,23,24,26,27]. They indicate that the biggest threat to the functioning of water supply networks will be changes related to the increase in temperature, intensifying hot periods, and drought [18,21,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant improvement in the hydraulic efficiency of traditional drainage systems was obtained as a result of the use of an innovative solution [70], whose idea resulted in the intentional installation of damming partitions across the direction of stormwater flow in gravity conduits of existing or planned drainage systems ( Figure 3). According to the features of the invention [70], the damming partition has an outflow orifice (4) in the bottom part, and the upper edge of the partition is a typical frontal overflow (2). For the analysis of the research on the hydraulic processes, an outflow orifice (4) with a circular cross-section was adopted, which was mapped in the SWMM program using the Orifice link function.…”
Section: Innovative Drainage Systems (Retention Sewage Canal)mentioning
confidence: 99%
“…Due to the increasing concentration of greenhouse gases in the atmosphere, climate changes cause significant transformations in the characteristics of extreme weather phenomena [1,2] manifested by an increase in the incidence of short-term torrential rainfall [3,4]. This implies a more frequent incidence of local urban floods, whose range shows great variability due to natural and human impacts, with particularly severe adverse effects in high-density urban catchments and a significant proportion of impervious surfaces [5][6][7].…”
Section: Introductionmentioning
confidence: 99%